PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN SIMULASI KOMPUTER TERHADAP HASIL BELAJAR SISWA SEKOLAH MENENGAH KEJURUAN DI GRESIK - Muafa, Ahsan; Ekohariadi, Ekohariadi; Santoso, Agus Budi (PENDIDIKAN VOKASI:TEORI DAN PRAKTIK, 2014)
AbstractThis research aims to study the effect of the use of computer simulation as a teaching media toward student?s learning achievement in vocational school. The focuses of the study are on the cognitive and psychomotor domains of the students in industrial electronics program and their responses toward the use of computer simulation as a teaching aid.The research was conducted under quasi experimental design with non equivalent control group pretest-postest model. The data on students? responses were analyzed using descriptive qualitative technique while the students? learning achievement scores were analyzed using quantitative techniques.The hypothesis of this research was tested using SPSS version 20 to get t-test score. The result of this research is in form of t-test score and its significance after being compared to the t table.The final score of student achievement from this calculation of the t-score is 11.673 with the sig value of 0.000. As the sig value is below 0.05 or 5%, it can be concluded that there is a significant difference between the score of learning achievement of the students who used computer simulation and those who use textbook. The analysis of students? responses toward the use of computer simulation as a teaching media indicates that computer simulation is a new media for the students and that this media is interesting for the students with the number of responses of 100 %.Keywords: Learning Media, Computer Simulation, Student Learning Achievement